2020
DOI: 10.2196/17517
|View full text |Cite
|
Sign up to set email alerts
|

Families’ Degree of Satisfaction With Pediatric Telehomecare: Interventional Prospective Pilot Study in Catalonia

Abstract: Background Pediatric home hospitalization improves the quality of life of children and their families, involving them in their children’s care, while favoring the work-life balance of the family. In this context, technology guarantees accessibility to assistance, which provides security to users. From the perspective of the health care system, this could lower the demand for hospital services and reduce hospitalization costs. Objective This study aimed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Seven studies (43.8%) [8] , [9] , [10] , [11] , [12] , [13] , [14] were intervention studies that introduced a new telehealth system that included a pulse oximeter and gathered user experience feedback. Two studies were case studies assessing the usability of a pulse oximeter in a healthcare context [15] , [16] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies (43.8%) [8] , [9] , [10] , [11] , [12] , [13] , [14] were intervention studies that introduced a new telehealth system that included a pulse oximeter and gathered user experience feedback. Two studies were case studies assessing the usability of a pulse oximeter in a healthcare context [15] , [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Four of the included studies (25%) examined the use of pulse oximeters as a tool to increase availability of care through pairing with a smartphone application [17] , [18] , [19] , [20] . Other applications included: as a diagnostic tool for children with pneumonia [15] , [16] ; a monitoring tool in paediatric telehomecare [11] ; remote risk-based monitoring tool for patients at risk of Cardiovascular disease (CVD) [8] , [10] ; a general monitoring tool for blood oxygenation levels [21] , [22] ; post-operative continuous vital sign monitoring for patients recovering from surgery [14] ; data capture and transmission to streamline clinical trials [9] ; long-term oxygen therapy (LTOT) optimization [12] ; and as a digital health intervention for managing Chronic Obstructive Pulmonary Disease (COPD) patients, either as a diagnostic tool or during rehabilitation [4] , [13] .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent systematic review that focuses on malignant and nonmalignant hematology concluded telemedicine provides similar or improved health care compared to face-to-face encounters in both pediatric and adult populations [ 29 ]. The readmission rate for home care was not significantly higher than for hospital care [ 20 ]. Additionally, in terms of satisfaction, a British study shows that 90% of parents and 63% of children stated a clear preference for home hospitalization, citing less psychosocial disruption and a perception that children recover more quickly with comfortable surroundings [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention and characteristics of the families who used the service has been documented in previous studies [ 20 ]. When the care team, whether from the hospitalization ward, outpatient department, or emergency department, detects a potential case of hospitalization at home, it contacts the referent of this program, which evaluates it according to the inclusion criteria (30 minutes of isochronous, clinical stability, voluntary consent, and adequate living conditions in the home).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation